MOLECULAR DOCKING AND THEORETICAL TOXICITY ASSESSMENT OF BIOACTIVE CONSTITUENTS OF LEAF AND ROOT BARK ESSENTIAL OILS FROM Spondia dulcis - Ekoro, Israel Azogor; Odeja, Oluwakayode Olubunmi (FUDMA Journal of Sciences, 2026)
Spondias dulcis (S. dulcis) belongs to the Anacardiaceae family that is also called Ambarella or golden apple. The medicinal uses of the plant have been reported. This study was conducted to investigate the phytochemical profile, antioxidant activity and the in silico drug discovery capability of the essential oil of the leaf and root bark of Spondia dulcis. Essential oils were obtained by hydro-distillation, and their compositions were determined using gas chromatography-mass spectrometry (GC-MS). The essential oil of the leaf (SDLEO) was found to be comprised of 30 compounds, with linalool and trans-β-ionone as major constituents, with concentrations of 35.06 and 11.48% respectively. In contrast, the SDREO contained 19 compounds, comprising p-cymene (44.03%) and o-acetyl-p-cresol (14.36%) as major compounds. Theoretical toxicity prediction on the pkCSM platform showed that several compounds were non-hepatotoxic and non-carcinogenic. Molecular docking of the antioxidant protein xanthine oxidase (PDB ID: 3NRZ) demonstrated good binding affinities, in which neophytadiene -5.6 kcal/mol) and farnesol -5.4 kcal/mol) had good binding affinities as compared to ascorbic acid -5.8 kcal/mol). These results indicate that S. dulcis essential oils displayed high antioxidant activity, and they contain bioactive non-toxic constituents for future pharmacological development.